PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TURNAMEN BERBANTUAN FLASHCARD UNTUK MENINGKATKAN KEMAMPUAN KERJASAMA MUATAN IPS KELAS IV SDN 182/1 HUTAN LINDUNG - Salsabila, Nabila; Astrid Senditia, Ai; Nurkhoeriah, Siti; Dzulqadri , Abraar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The objective of this study was to determine how well the participant's collaborative skills are on an IPS load using a cooperative Team Games Tournament (TGT) model supported by a flash card. The PTK (Class Action Research) study was conducted in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. 20 students of Class IV SDN 182/1 Protected Forests are the subject of this research. Techniques of data collection without testing and data analysis include evaluating the participant's collaborative skills in learning. This class action research was considered successful because the student's collaborative skill results reached 75% of the students of the fourth grade with the predicate